2007
DOI: 10.1002/cmdc.200600274
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Study on the Spatial Arrangement of the Third Aromatic Ring of Endomorphins 1 and 2 Using an Atypical Constrained C Terminus

Abstract: The discovery of endomorphins (EMs) has opened the possibility of searching for new analgesics. However, the design of peptide analgesics has proven to be very difficult as a result of their conformational flexibility and a lack of clarity in structure-activity relationships (SAR). In EMs, the amino acid side chains exhibit considerable conformational flexibility, especially in the third aromatic ring, which is free to adopt a bioactive conformation. To resolve these problems, a series of C terminus EM analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
(75 reference statements)
0
22
0
1
Order By: Relevance
“…Thus, we concluded that EM-1-NHNH 2 showed an agonist property relative to EM-1, while EM-2-NHNH 2 probably acted as a partial agonist relative to its parent EM-2. Thus, C-terminal amidation would largely influence the molecular conformation of a bioactive peptide and its interactions with receptor Yu et al, 2007a). Moreover, the antinociceptive effects of these compounds were inhibited by naloxone, indicating an opioid mechanism.…”
Section: Peptidementioning
confidence: 97%
“…Thus, we concluded that EM-1-NHNH 2 showed an agonist property relative to EM-1, while EM-2-NHNH 2 probably acted as a partial agonist relative to its parent EM-2. Thus, C-terminal amidation would largely influence the molecular conformation of a bioactive peptide and its interactions with receptor Yu et al, 2007a). Moreover, the antinociceptive effects of these compounds were inhibited by naloxone, indicating an opioid mechanism.…”
Section: Peptidementioning
confidence: 97%
“…The much lower activity shown by 5 , as compared to the Trp3 containing analogue [3Aze 2 ]EM-1 ( 4 ), can be interpreted on the basis of the well recognized role of the aromatic residues on ligand-receptor interactions. Several studies on EM-1 and EM-2 clearly show that aromatic side chains with different size, distinct noncovalent interactions and H-bonding capability, can highly influence conformations43 and binding 21,44,45. Results of ligands 4 and 5 indicate that the beneficial effect on the activity, constantly observed in EM analogues containing the indole ring system at position 3, gives results that are particularly efficient as compared to the Phe3 residue in models containing the achiral 3Aze residue.…”
mentioning
confidence: 99%
“…Nevertheless, not only the afore-mentioned L-D isomerism produces an effect on the structural properties and bioactivity of EM2, but the cis-trans isomerism affects also the conformational features and affinity of this tetrapeptide. Namely, as the results obtained from the earlier studies pointed out, the EM2 and its structurally modified derivatives existed as an equilibrium mixture of the cis-and trans-isomers regarding the Tyr (14). Although the previous studies supported the presence either of the trans or of the cis Tyr 1 -Pro 2 peptide bond in the biologically active form of EMs, it is important to note that the isomerization state of this peptide bond concerning the bioactive conformation of EM1 and EM2 is still obscure (5).…”
mentioning
confidence: 86%
“…Based on the three ranges of tc region, it could be deduced that three different groups of cis-trans stereoisomer pairs could be distinguished, which were characterized by high, moderate, and low similarities, respectively, as follows. The first group with the range of 0.74-0.81 included four different types of peptide pairs containing certain tripeptide units, i.e., (i) the trans-(Y Table 2), [14]). For the former case, the g ()) rotamer was mainly favored (i.e., a g (+) ⁄ g ()) ⁄ trans ratio of circa 20% ⁄ 60% ⁄ 20%), while for the latter one, the g (+) rotamer was mostly preferred (i.e., a g (+) ⁄ g ()) ⁄ trans ratio of circa 60% ⁄ 20% ⁄ 20%), regarding the side chain of Y 1 ⁄ y 1 amino acid.…”
Section: U-w and V Conformational Spacesmentioning
confidence: 99%
See 1 more Smart Citation